Impact of subjective performance appraisal and bonus allocation on attitudes of lower level managers. - Low, Emily Ju-Lee. (2008)
The present research attempts to provide a deeper understanding of these two areas by analysing the relationship existing between the performance appraisal process variables and employee affective reactions of trust and confidence, goal commitment as well as voluntary turnover intention. These reactions were investigated in a 2 X 3 factorial designed experiment, in which 105 subjects completed a questionnaire assessing the above dependent variables.